Increasing the Rates of Postpartum Measles, Rubella, and Varicella Vaccination in Nonimmune Mothers: An Electronic Medical Record-Based Quality Improvement Intervention - Park, Jiwoo; Kwon, Daniel Y.; Sue, Rachel; Bahl, Kajol; Wang, Anya; Gamboa, Sophia; Linker, Anne S.; Aoun, Reem; Abraham, Cynthia (American Journal of Perinatology, 2025)
Postpartum measles, mumps, rubella (MMR), and varicella vaccination is critical for nonimmune mothers to prevent severe maternal and neonatal complications. Despite recommendations, vaccination rates remain suboptimal, particularly in completing the two-dose series. This study evaluates the impact of an electronic medical record (EMR)-based intervention on postpartum MMR and varicella vaccination rates.A retrospective cohort study was conducted at two urban tertiary care centers. Nonimmune postpartum patients with public insurance who delivered between January 2021 and June 2022 and February 2023 and October 2024 were included in the pre- and postintervention groups, respectively. The intervention, implemented in April 2023, modified the mandated postpartum checklist in the EMR to include measles immunity status and emphasize the necessity of completing the two-dose series for MMR and varicella. The primary outcome was the completion rate of the two-dose series, with secondary outcomes assessing provider adherence and patient acceptance. Statistical analyses included chi-squared and t-tests to compare pre- and postintervention cohorts.A total of 468 patients were included (220 preintervention and 248 postintervention). MMR series completion significantly increased from 2.3 to 34.9% (p < 0.001). Varicella series completion showed a nonsignificant upward trend from 27.0 to 36.5% (p = 0.112). Provider adherence improved, with fewer missed opportunities to offer the second dose at the postpartum visit (49.6 vs. 32.9%; p = 0.004 for MMR). Patient declination rates remained stable.Integrating vaccination reminders into the EMR significantly improved postpartum MMR series completion. While varicella rates showed a modest increase, persistent provider follow-up and patient education remain crucial. Future efforts should focus on addressing systemic barriers and enhancing patient outreach to further optimize postpartum vaccination completion.
Keywords: measles; rubella; varicella; postpartum vaccination; quality improvement; electronic medical record